Economic policy uncertainty and foreign direct investment: The role of social connectedness in Vietnam - Nguyen, Thu Ha; Nguyen, Truong Giang; Nguyen, Cao Chuong (Economic Journal of Emerging Markets, 2025)
Purpose — This study examines the association between home countries’ economic policy uncertainty (EPU) and foreign direct investment (FDI) inflows into Vietnam. It also investigates how social connections between home countries and Vietnam, measured by the Social Connectedness Index, moderate the EPU—FDI relationship.Method — Using data from 12 home countries from 2011 to 2022, this study analyzes the impact of EPU on FDI inflows through regression models, incorporating the social connectedness index to explore moderating effects.Findings — The results show that higher EPU significantly leads to lower FDI inflows into Vietnam. Social connectedness mitigates the negative impact of EPU on FDI by reducing information friction and enhancing trust in uncertain policy environments. These results are robust for home countries that experience periods of high global uncertainty and geopolitical risk and are members of APEC.Implications — The findings suggest that both the home and host countries should focus on stabilizing their policies and leveraging social connections to mitigate the negative impact of policy uncertainty, which could improve policymaking and investment strategies.Originality — This research uniquely examines how EPU in home countries affects FDI in a specific emerging country, Vietnam. It introduces social connections as a moderating factor, offering new insights into the interplay between policy uncertainty and international investment behavior.